Modulation of the allosteric and vasoregulatory arms of erythrocytic oxygen transport - Wise, Thomas J.; Ott, Maura E.; Joseph, Mahalah S.; Welsby, Ian J.; Darrow, Cole C.; McMahon, Tim J. (Frontiers in Physiology, 2024)
ABSTRACT Efficient distribution of oxygen (O2) to the tissues in mammals depends on the evolved ability of red blood cell (RBC) hemoglobin (Hb) to sense not only O2 levels, but metabolic cues such as pH, PCO2, and organic phosphates, and then dispense or take up oxygen accordingly. O2 delivery is the product of not only oxygen release from RBCs, but also blood flow, which itself is also governed by vasoactive molecular mediators exported by RBCs. These vascular signals, including ATP and S-nitrosothiols (SNOs) are produced and exported as a function of the oxygen and metabolic milieu, and then fine-tune peripheral metabolism through context-sensitive vasoregulation. Emerging and repurposed RBC-oriented therapeutics can modulate either or both of these allosteric and vasoregulatory activities, with a single molecule or other intervention influencing both arms of O2 transport in some cases. For example, organic phosphate repletion of stored RBCs boosts the negative allosteric effector 2,3 biphosphoglycerate (BPG) as well as the anti-adhesive molecule ATP. In sickle cell disease, aromatic aldehydes such as voxelotor can disfavor sickling by increasing O2 affinity, and in newer generations, these molecules have been coupled to vasoactive nitric oxide (NO)-releasing adducts. Activation of RBC pyruvate kinase also promotes a left shift in oxygen binding by consuming and lowering BPG, while increasing the ATP available for cell health and export on demand. Further translational and clinical investigation of these novel allosteric and/or vasoregulatory approaches to modulating O2 transport are expected to yield new insights and improve the ability to correct or compensate for anemia and other O2 delivery deficits.